Increasing ADR reporting in Nepal - Shankar, Ravi P (Nepal Journal of Epidemiology, 2013)
Not all publications relating to pharmacovigilance in the country have been highlighted in the manuscript. The criteria which the authors followed for selecting and citing references can be explained. Strengthening pharmaco- vigilance in Nepal is an essential but daunting task with tremendous implications for patient safety and rational use of medicines. DOI: http://doi.dx.org/10.3126/nje.v3i2.8511